Conversational Roles, Generational Differences and the Emergence of Historical and Personal Memories Surrounding WWII during Familial Discussions. Issue 7 (9th August 2022) - van der Haegen, Aurélie; Stone, Charles B.; Luminet, Olivier; Hirst, William
ABSTRACT: We examined whether and how conversational roles shape the extent to which details and recollections surrounding World War II (WWII) emerge in family conversations. Each family was tasked with collaboratively discussing four topics surrounding WWII specific to Belgium. We then conducted both quantitative and qualitative analyses. The former compared the collaborative recall with each family member's individual recall; the latter focused on the conversational roles and dynamics within each family. While the results suggest that familial discussions lead to more "old" (from the individual recollection) recollections than "new" recollections, about 40% new recollections did emerge; however, with fewer personal details surrounding the discussed recollections. Although, the extent to which more details and new recollections emerged during the conversations across families depended on the conversational roles adopted by each discussant. Our results are discussed in terms of the importance of conversational roles in understanding when and how memories may emerge within a conversation and, in turn, transmit across generations.